Theoretical study of a novel refrigeration compressor - Part III : leakage loss of the Revolving Vane (RV) compressor and a comparison with that of the rolling piston type - Teh, Yong Liang (2009)
A new refrigeration compressor, named ‘Revolving Vane (RV) compressor’, has been introduced in Part I of this paper series. The efficiency of the RV compressor, alike other refrigeration compressors, is primarily affected by mechanical and leakage losses, amongst which the former has been